Vigorexia: uma leitura psicanalítica - Feitosa Filho, Odimar Araújo (2008)
This study concerns to muscular dystrophy, also knows overtraining. The research considers that overtraining is not a psychoanalytic concept, but that it is possible to make both approches closer through freudo-lacanian psychoanalysis. So, this work aims at analyzing, from psychoanalytic research, the purpose of creating a subtype of body dysmorphic disorder, as well as searching to recognize which kind of discourse is within symptom social bond of that individuals who show a clear distortion in their body image, which make them feel weak and small, when, in fact, they are very strong and brawny, leading them into an obsession to reach a “perfect” body. From such subjects’ relationship with wish and enjoyment, this study argues on the relationship between overtraining and current imperatives of enjoyment focusing on a male body that is brawny and in shape. The study considers that one cannot talk about overtraining as a category to psychoanalysis, since it has to be treated as a symptom; as an expression of cultural distress; as a manifestation of enjoyment real, that comes back; as a contemporary way man found for questioning about maleness; and, primarily, as a way subject finds to face civilizatory ideals that require body’s surrendering. The research concludes that freudo-lacanian psychoanalysis can introduce a theorization on such symptomatology etiology, without needing to create new categories, both inside theory, or to use psychiatric categorization. The work shows a straight articulation between the graduating student discourse and the overtraining symptoms, but it is not possible to assert that individuals showing overtraining symptoms are necessarily obsessive neurotic, although there can be a strong appeal for obsessions formation within searching for ideal body. In such sense, the study designs a discussion on how overtraining symptoms can emerge within obsessive neurosis and hysteria, not excluding its possibility to be present in perversion or psychosis.